Answer:
what is this......................
18 = 4 × 4 + 4 −√4 = (44 ÷ √4) − 4
Step-by-step explanation:
By rule of bodmas rule
= 1 - 31 + 6 + 3 × 8
= 1 - 31 + 6 + 24
= 1 - 31 + 5 + 24
= - 30 + 5 + 24
= - 25 + 24
= -1
Now without using bodmas rule
= 1 - 31 + 6 + (4 - 1). 8.
=-30+6+4+(4-1)×8
=-23+4+(4-1)×8
=-19+4+(4-1)×8
=-15+(4-1)×8
=-15+3×8
=-15+24
=-9
MARK AS BRAINLIST IF IT IS USEFUL
<u>Solution:</u>
Substitute the value of the variable into the expression, then simplify.
Answer: -8
_________________________________________________________
Hope this helps! If so, lmk! Thanks and good luck!